Students’ perception and expectation toward learning German receptive skills - Karuna, Kalvin; Serpara, Henderika; Nikijuluw, Maria Martha (Journal of Education and Learning (EduLearn), 2025)
The purpose of this study is to describe the perceptions and expectations of German language students, especially in terms of receptive skills. This study asks two main questions: i) what are the expectations of students towards learning German and ii) how are students' perceptions of German learning, especially reading and listening, the data sources for this research are students of the German Language Education Study Program. The research instruments were questionnaires and in-depth interviews. The data were analyzed descriptively, which showed that i) In general (98%) students have high expectations to study and work in Germany, for example, following the "Ausbildung," ii) 98% of students realize that reading and listening are ways to broaden horizons, enrich vocabulary, and avoid misunderstandings in both one-way and two-way communication; and iii) Students' cognitive perceptions of reading and listening skills contribute to their positive attitudes towards improving these receptive skills; this finding shows that positive perceptions and high expectations of students are inversely proportional to their receptive abilities.